Love story - Zaninelli, Martina; Mazzi, Antonio; Ruffo, Giambattista (Genova : Edicolors, 2004)
Illustrazioni di Martina ZaninelliIntroduzione di Don Antonio Mazzi
Keywords: Omosessualità -- Libri per ragazzi